Identification of colloidal haze protein in Chinese rice wine (Shaoxing Huangjiu) mainly by matrix‐assisted laser ionization time‐of‐flight mass spectrometry. Issue 8 (23rd June 2020) - Xie, Guangfa; Han, Jiongping; Han, Xueyuan; Peng, Qi; Fu, Jianwei; Shen, Chi; Sun, Jianqiu; Sun, Junyong; Lu, Jian; Lu, Yin; Li, Guolong
Abstract: As one of the three most famous brewed wines in the world, Chinese rice wine is made from rice and husked millet, containing 14 percent to 20 percent alcohol. Highly original, yellow wine brewing techniques are regarded as the model of the wine brewing industry in Asia. Shaoxing Huangjiu is produced in Zhejiang province and remains the oldest and most representative Chinese rice wine. During storage, Shaoxing Huangjiu is susceptible to environmental disturbance and produces colloidal haze to result in turbidity. In this study, the main composition and source of colloidal haze protein in Shaoxing Huangjiu were analyzed by two‐dimensional electrophoresis and matrix‐assisted laser ionization time‐of‐flight tandem mass spectrometry (MALDI‐TOF/TOF MS). The results showed that the proteins in colloidal haze mainly consisted of oat protein b1, oat‐like protein, di‐amylase inhibitor, pathogenesis‐related protein, pathogenesis‐related protein‐4, chitinase II derived from wheat and oat‐like protein, and beta‐amylase derived from rice. The amino acid composition and secondary structure of haze protein and supernatant protein in Huangjiu were further explored by high‐performance liquid chromatography and Fourier transform infrared spectroscopy. The study has broadened knowledge of the main composition and source of colloidal haze protein in Shaoxing Huangjiu. The corresponding results indicated that the amino acid composition from colloidal haze had the main characteristics of high hydrophobicity and low water solubility. Abstract : In this study, the main composition and source of colloidal haze protein in Chinese rice wine (Shaoxing Huangjiu) were analyzed by two‐dimensional electrophoresis and matrix‐assisted laser ionization time‐of‐flight tandem mass spectrometry (MALDI‐TOF/TOF MS). Meanwhile, the amino acid composition and secondary structure of haze protein and supernatant protein in Huangjiu were further explored by high‐performance liquid chromatography and Fourier transform infrared spectroscopy.